GLUEBALLS - Jenkovszky, L.; Shpenik, A.; Svintozelskyi, V. (Одеські астрономічні публікації, 2019)
Glueball and oddball resonances lying on the pomeron/odderon trajectories (Chew-Frautchi plot) with threshold and asymptotic behaviour re- quired by analyticity and unitarity are predicted. The parameters of the pomeron and odderon trajectories are fitted to the data on high-energy elastic proton- proton scattering. The fitted trajectories are extrap- olated to the resonance region to predict masses and widths of glueballs and oddballs. Appended by unitary symmetry, the Chew-Frautchi plot remains a powerful tool to classify hadrons.